Total phenolic, flavonoid contents and antioxidant activity of tamarind seed and pulp extracts - Phuong Ha, Le; Van Ngoc, Nguyen; Trang Huyen, Nguyen Thi; Thu Hang, Le Thi; Kieu Oanh, Nguyen Thi; Tuyet, Tran Thi; Mai Phuong, Nguyen Thi; Minh Hong, Nguyen Thi (Vietnam Journal of Biotechnology, 2022)
Tamarind (Tamarindus indica) has long been known for its high nutrition content and pharmacological potential. However, there is lack of studies on the content of antioxidants, phenolic and flavonoid contents of tamarind seed grown in Vietnam. Thus, the aim of this study was to compare the seeds and pulps of Tamarindus indica from three different areas across Vietnam including Son La, Hai Phong and Sai Gon with regard to the total phenolic content (TPC), total flavonoid content (TFC) and antioxidant activity of their water and methanol extracts, as well as their cytotoxicity on a normal BKH-21cells. TPC and TFC were evaluated by the Folin–Ciocalteu reagent and aluminum chloride, respectively. The 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2’-azinobis (3-ethylbenzothiazoline-6-sulfonic acid (ABTS) radical scavenging assays were used to investigate antioxidant capacity. The safety of T. indica extracts was assessed by using MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assay. Our results showed that the methanolic extracts yielded higher TPC (742.919 ± 50.360 mg GAE/g extract), TFC (68.492 ± 0.023 mg QE/g extract) and possessed stronger free radical scavenging activity (IC50 of 52.5 µg/mL) compared to that of water extracts. T. indica seeds from all three regions possessed higher TPC, TFC and antioxidant activity than those of pulps. Regarding the safety, in vitro analysis showed that tamarind seed and pulp extracts only became toxic to BHK-21 cell line at a very high concentration with IC50 values range from 143.77 µg/mL to 620.35 µg/mL. This study revealed that T. indica seeds and pulps can serve as functional food as well as potential antioxidants in pharmaceutical products.